2018
DOI: 10.1053/j.gastro.2017.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Historical Perspectives and Advances in Mesenchymal Stem Cell Research for the Treatment of Liver Diseases

Abstract: Liver transplantation is the only effective therapy for patients with decompensated cirrhosis and fulminant liver failure. However, due to a shortage of donor livers and complications associated with immune suppression, there is an urgent need for new therapeutic strategies for patients with end-stage liver diseases. Given their unique function in self-renewal and differentiation potential, stem cells might be used to regenerate damaged liver tissue. Recent studies have shown that stem cell-based therapies can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 146 publications
2
63
0
Order By: Relevance
“…Subsequently, it was found that such cells can differentiate into different cellular types and tissues of mesenchymal origin, like bone, fat, and cartilage (Pittenger et al, 1999). Interestingly, it has been recently reported that such cells can be also induced to differentiate into cells of endodermic and ectodermic origin, like hepatocytes and neurons, respectively (Lee et al, 2018a;Marei et al, 2018).…”
Section: Properties and Therapeutic Potential Of Mscmentioning
confidence: 99%
“…Subsequently, it was found that such cells can differentiate into different cellular types and tissues of mesenchymal origin, like bone, fat, and cartilage (Pittenger et al, 1999). Interestingly, it has been recently reported that such cells can be also induced to differentiate into cells of endodermic and ectodermic origin, like hepatocytes and neurons, respectively (Lee et al, 2018a;Marei et al, 2018).…”
Section: Properties and Therapeutic Potential Of Mscmentioning
confidence: 99%
“…They also secrete various growth factors and cytokines that promote cell regeneration, tissue repair, and immune regulation. MSCs have been used in mouse models for the treatment of a variety of diseases, including acute lung injury, myocardial infarction, diabetes, sepsis, liver dysfunction, and acute renal failure [4,5]. Since MSCs have shown promising clinical application prospects in animal models of human diseases, MSCbased therapies have been carried out in multiple clinical trials for the treatment of various disorders [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…As shown on www.ClinicalTrials.gov, dozens of MSC-based clinical therapies are underway for different types of liver injury, including autoimmune hepatitis, alcoholic liver cirrhosis, and liver fibrosis. However, MSC-based therapies have been strongly limited by their unclear mechanism of action [5,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, this therapy is limited by the rarity of donor livers and the poor systemic condition of patients before surgery due to long waiting time [2]. Preliminary researches indicate that stem cells play an key role in the treatment of ALF through transdifferentiating into hepatocytes to perform alternative functions, promote liver regeneration, reduce hepatocytes apoptosis, inhibit liver fibrosis, and regulate the immune and inflammatory response [3][4][5][6]. Based on importance of immune responses in ALF, the immune regulation of stem cells may be the most important factor in the treatment of ALF [7].…”
Section: Introductionmentioning
confidence: 99%